Book review: An Encyclopedic Dictionary of Language Testing, 5th edition - Santos, Victor D. O. (Language testing, 2014)
[...]some more recent terms such as CEFR (officially published in 2001) are only present in EDLT. [...]EDLT contains a higher concentration of statistical terms and alternative names for terms, which naturally increases the number of entries found therein. [...]we can conclude that the true encyclopedic nature of EDLT is due not to a larger coverage of relevant and purely language-testing-related terms. [...]EDLT would benefit from two additions: a 138 Language Testing 31(1) higher percentage of references from the past 10 years (the majority of the references are from the 1970s, 1980s, or 1990s) and the inclusion, at the end, of a subject index, as one can find in Davies et al.s dictionary. The terms chosen are readability, reading comprehension, prochievement test, discrete-point test, semi-direct test, SOPI, OPI, Modern Language Aptitude Test, trialing, First Certificate of English, unitary competency hypothesis, CALT, Interagency Language Roundtable (proficiency) scale, CEFR, Critical Language Testing, evidence-centered design, TOEFL, English for Specific Purposes, fluency, IELTS, LTRC, lexical density, ACTFL, and target language.